Effect of strategic gastrointestinal nematode control on faecal egg count in traditional west African cattle - (:unkn) unknown (My University, 2000)
This paper reports on the effect of strategic anthelmintic treatments and other determinants on faecal egg counts (FEC) of Trichostrongyles in N'Dama cattle of a west African village. Initially, 527 animals from 13 private N'Dama cattle herds were monitored in a longitudinal study from October 1989 to December 1994. Each herd was stratified by age and animals were sequentially allocated to two groups with similar age distributions. One group received a single anthelmintic treatment of fenbendazole (7.5 mg/kg BW), in October 1989 (n = 250), whereas the other group remained untreated (n = 277) throughout the study. In the next rainy season (June to October), the treated animals were treated twice (in July and September). The same treatment schedule was used in the subsequent rainy seasons until December 1994. Biannual anthelmintic treatments decreased the level of FEC between 31% (late dry season) and 57 of FEC were found during the rainy season from June to October. FEC levels decreased until 4 years of age, after which they remained on a constant low level. The variability of returns to anthelmintic treatments between herds did not seem to be influenced by FEC at the herd level. The financial evaluation of anthelmintic interventions cannot be predicted from FEC and must necessarily rely on the direct monitoring of livestock productivity parameters.
Keywords: African Research